Association analysis of biotic and abiotic stresses resistance in chickpea (Cicer spp.) using AFLP markers - Ali Saeed; Reza Darvishzadeh (Biotechnology & Biotechnological Equipment, 2017)
Chickpea suffers from different biotic and abiotic stresses, which has led to considerable decreases in seed yield. Since the economic value of a cultivar is determined by its phenotypic characteristics, good knowledge of the genetic structure and identification of genomic loci associated with desired traits will facilitate crop breeding. Amplified fragment length polymorphism (AFLP) markers associated with different agro-morphological characteristics, cold and drought tolerance as well as Ascochyta blight resistance were identified in chickpea by using 44 genotypes comprising cultigens, landraces, internationally developed improved lines and wild relatives, evaluated in a randomized complete block design with three replications at the Urmia rainfed research station. Using six AFLP primer combinations, 64 clear and reproducible markers were developed. The polymorphism information content values calculated for each primer pair ranged from 0.155 (EcoR1-ACC/Mse1-CAG) to 0.270 (EcoR1-ACC/ Mse1-CTG) with an average of 0.237. Analysis of molecular variance (AMOVA) revealed that 90% of the total variance was due to differences within populations and 10% due to differences among populations. Using a general linear model and applying multiple testing corrections, 24 AFLP markers associated with genes controlling the studied traits were identified. Some identified markers were associated with more than one trait. The identified markers could be of interest in marker-assisted selection in chickpea breeding programmes.